FODMAPs: food composition, defining cutoff values and international application. (March 2017) - Varney, Jane; Barrett, Jacqueline; Scarlata, Kate; Catsos, Patsy; Gibson, Peter R; Muir, Jane G
Abstract: The low‐FODMAP diet is a new dietary therapy for the management of irritable bowel syndrome that is gaining in popularity around the world. Developing the low‐FODMAP diet required not only extensive food composition data but also the establishment of "cutoff values" to classify foods as low‐FODMAP. These cutoff values relate to each particular FODMAP present in a food, including oligosaccharides (fructans and galacto‐oligosaccharides), sugar polyols (mannitol and sorbitol), lactose, and fructose in excess of glucose. Cutoff values were derived by considering the FODMAP levels in typical serving sizes of foods that commonly trigger symptoms in individuals with irritable bowel syndrome, as well as foods that were generally well tolerated. The reliability of these FODMAP cutoff values has been tested in a number of dietary studies. The development of the techniques to quantify the FODMAP content of foods has greatly advanced our understanding of food composition. FODMAP composition is affected by food processing techniques and ingredient selection. In the USA, the use of high‐fructose corn syrups may contribute to the higher FODMAP levels detected (via excess fructose) in some processed foods. Because food processing techniques and ingredients can vary between countries, more comprehensive food composition data are needed for this diet to be more easily implemented internationally.